Peran Kelompok Tani Dalam Meningkatkan Produktivitas Padi Sawah di Desa Kedung Pengawas Kecamatan Babelan Kabupaten Bekasi - Wibisono, Fariz Hamzah; Kuswarini, Kuswarini; Melani, Ana (Jurnal Ilmiah Wahana Pendidikan, 2025)
Kedung Supervisor Village is one of the villages in Babelan District that produces rice. In 2019, the Kedung Village Supervisor had an agricultural area of 320 ha producing 5.5 tonnes/ha of rice. Meanwhile, in 2022, Kedung Supervisory Village experienced a shrinking harvest area and a decrease in productivity, namely with a harvest area of 229.2 ha producing 4.5 tons/ha. There are nine farmer groups in Kedung Supervisory Village, however four farmer groups are still at the beginner class stage and five farmer groups are advanced class. Thus, the role of farmer groups is needed in increasing rice productivity in Kedung Supervisory Village. The aim of this research is to analyze the level of role of farmer groups and the relationship between the role of farmer groups in increasing rice productivity. Research is quantitative and qualitative research. The sampling technique in this research used a proportional random sampling technique to obtain 70 people. Primary data is by means of observation and interviews or the results of filling out questionnaires that have been provided by the researcher. The data analysis used was Likert scale, category, descriptive, t test, and Spearman Rank correlation. The research results found that the level of role of farmer groups as a whole was included in the medium category (Score 3.2). Includes roles: learning vehicle, collaboration, production unit in the medium category with respective scores: 3.2, 3.2, 3.1. There is a relationship between the role of farmer groups and the productivity of lowland rice farming. From the results of the T test, t_{count} 4.354 is greater than t_{table} 1.666. Therefore, H_0 is rejected and H_1 is accepted, with the strength of the relationship (correlation) being very weak because the correlation coefficient is 0.080